"But I Ain't a Judge:" The Therapeutic Jurisprudence Implications of the Use of Nonjudicial Officers in Criminal Justice Cases. (November 2020) - Perlin, Michael L.
The role of nonjudicial officers occupies a hidden space in the U.S. judicial system. Statutorily sanctioned in many jurisdictions, such officers have a wide range of duties and responsibilities, including hearing certain pretrial motions in criminal cases and making decisions as to conditions of probation for sex offenders. These latter officers are frequently not lawyers, and there is significant evidence that many of the basic rudiments of the criminal trial process are often not honored. There has been virtually no consideration of this phenomenon in the scholarly literature, and absolutely no consideration from the perspective of therapeutic jurisprudence (TJ). An investigation into TJ's basic inquiry into whether legal rules, procedures, and lawyer roles need to be reshaped suggests that TJ is not practiced in the systems under discussion here.